Securing Wireless Networks Against Emerging Threats: An Overview of Protocols and Solutions - Lakhani, Rishit; Sachan, Ram Chandra (Journal of Science & Technology, 2024)
As wireless networks have become an integral part of modern communication infrastructure, ensuring their security against a rapidly evolving threat landscape is a critical concern. This research article provides a comprehensive overview of the emerging threats targeting wireless networks, including advanced persistent threats, man-in-the-middle (MitM) attacks, and AI-driven adaptive malware. With the advent of new technologies such as 5G, the Internet of Things (IoT), and artificial intelligence (AI), the attack surface for wireless networks has significantly expanded, demanding more robust and adaptive security protocols.The paper analyzes the efficacy of current wireless security protocols, such as WPA3 and the 802.11i standard, in addressing these emerging vulnerabilities. While these protocols have introduced significant improvements, they are not without limitations. The article further explores innovative solutions such as blockchain-based security frameworks, AI-powered threat detection systems, and the future potential of quantum cryptography in safeguarding wireless communications.Through a critical review of recent case studies and empirical data, the article highlights the key challenges that organizations face in securing wireless networks, particularly in IoT environments where security standards lag behind technological advancements. The research concludes that while existing protocols provide foundational security, they must be continuously updated and augmented with cutting-edge technologies to counter the growing sophistication of cyberattacks.This article aims to provide insights into the state of wireless network security and offer practical recommendations for enhancing security protocols. Future research directions are also discussed, focusing on the integration of AI-driven threat intelligence and the standardization of security protocols across various wireless technologies. The findings underscore the importance of proactive security measures to safeguard wireless networks in an increasingly interconnected world.
Keywords: Wireless Security; Emerging Threats; WPA3; Internet of Things (IoT); Cybersecurity Protocols; Blockchain Security; Artificial Intelligence; Threat Detection; 5G Networks; Cryptographic Protocols